RESPON KRISIS HUMAS RESTORAN CEPAT SAJI DALAM MENGHADAPI ISU KONFLIK TIMUR TENGAH - Dwi Ayuni, Risa; Akbar Hayat, Muzahid; Sanusi; Apriliyanti, Rizki; Rico (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
Reputational crises are a significant challenge for multinational companies, especially when dealing with geopolitical issues such as the Israel-Palestine conflict. This article explores McDonald’s crisis response to allegations of involvement in the conflict and its impact on the company’s global reputation. Using a qualitative approach with content analysis of media texts published from January to June 2024, this study finds that McDonald’s strategic move in overcoming the crisis, namely taking over control of the franchise operations in Israel, was an important effort to mitigate the negative impact on their image. In addition, this article highlights the important role of transparent and proactive crisis communication in managing public perception amidst complex geopolitical situations. In conclusion, with the implementation of appropriate crisis management, including direct control of potential crisis triggers and effective communication, companies can maintain their reputation in an increasingly complex global market. The findings of this study offer insights for other multinational companies in developing adaptive and responsive strategies to the dynamics of crises triggered by geopolitical conflicts. Keywords: Crisis, Public Relations, Reputation, Conflict, Media